Facial Nerve Function after the Extended Translabyrinthine Approach - Miller, Mia E.; Mastrodimos, Bill; Cueva, Roberto A. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objective To evaluate facial nerve function after excision of petroclival/anterior cerebellopontine angle (CPA) meningiomas by the extended translabyrinthine (EXTL) approach and compare these with outcomes after the transcochlear and transotic approaches.Design Retrospective chart review.Setting/Participants A search of archived surgical cases at a single institution between January 1, 1995, and January 1, 2012.Main Outcome Measures Facial function measured on the House-Brackmann (HB) scale.Results A total of 16 patients underwent the EXTL approach for primary excision of petroclival meningiomas. Average tumor size was 4.6 cm, and six patients had gross total resection. Average length of follow-up was 36.4 months. Two patients required reoperation for tumor regrowth. Preoperative facial function was HB I or II in all patients with available examinations. Immediate postoperative facial nerve function ranged from HB I to HB VI. In patients with an intact facial nerve at surgery, all but one had long-term facial function of HB I or II. A robust response on intraoperative facial nerve monitoring was prognostic of favorable long-term facial function. Facial function declined in some patients after postoperative radiation or revision surgery.Conclusions The EXTL approach allows excellent exposure of petroclival/anterior CPA lesions and should be favored to improve facial outcomes.
Keywords: facial paralysis; meningioma; petroclival junction; cerebellopontine angle